Line Balancing Method As An Effort To Improve Cable Production In Pt Kmi Wire And Cable Production Management - Suparmin; Saragih, Yuliarman (Publisher Cv. Inara, 2023)
Write Line Inner Sheating at PT. KMI Wire and Cable has idle time due to processing time on Unbalanced work stations sometimes cause stop lines. Fromcalculations it is known that the cycle time gap / cycle time obtained is as big as 109.2 seconds and the figure is taken based on the biggest time from 6 stations existing work. The author intends to examine the causes of its occurrence processing time delays that occur on the Inner Sheating line and deliver give suggestions for future improvements. This research uses line balancing method and production system layouts. Among them is looking for the cycle time at the 6 largest stations as a reference in determining the next calculation, calculating the company's capacity, determining the efficiency of the machine, calculating the number of machines, adding the number of machines and additional floor area. Data is taken from field observations and records. The author uses two methods, namely the line balancing method and the system method production layout. he line balancing method and production layout system that has been carried out can be causing it to be able to meet market demand of 17,688 coils / month with the addition of machines / work stations, the required floor area is 14 m² with details, 7 m² at the Inner Sheat workstation and 7m² at the Outer Sheat station.